Functional characterization of the MdMYB73L gene in drought and salt stress tolerance in apple - Xiao-Wen Li; Han-Yu Dong; Ya-Qi Liu; Jing-Yi Su; Xue Wang; Chang Li; Qi-Fei Wu; Wen-Xian Zhang; Xin-Rong Shi; Hong-Jian Cao; Qiangbo Liu; Xiao-Fei Wang; et al. (Plant Molecular Biology, 2026)

Cloning and functional analysis of MdCRCT1 in the regulation of drought tolerance in apple - Xiao-Wen Li; Ya-Qi Liu; Jing-Yi Su; Xin-Rong Shi; Chang Li; Xue Wang; Qi-Fei Wu; Xuan He; Hong-Jian Cao; Xiao-Fei Wang; Ting-Ting Zhang (Physiology and Molecular Biology of Plants, 2026)

Increasing phosphorus availability and dynamics enhance soil organic carbon and its sub-pools sequestration as consequence of phosphorus inputs - Yao Liu; Junru Li; Ning Su; Xiangmin Rong; Yuping Zhang; Xianjun Zeng; Jianwei Peng; Gongwen Luo (Soil Ecology Letters, 2026)

Nitrogen fertilization simultaneously strengthens soil carbon and nitrogen pools, with implications for productivity gain of double-cropping rice system - Junru Li; Yao Liu; Hao Huang; Ning Su; Qiulong Hu; Xiangmin Rong; Yuping Zhang; Jianwei Peng; Gongwen Luo (Biology and Fertility of Soils, 2026)

Phytochemistry, pharmacology and bibliometrics insight of the genus Callicarpa L.: an extensive review encompassing the years from approximately 2010 to 2024 - Wang Jiang; Si-Rong Huang; Wen-Jie Ma; Yi-Qiu Yi; Ping Li; Zhong-Hui Ma; Zhi-Wei Su (Phytochemistry Reviews, 2026)

Anti-cancer effects of Psoralea corylifolia: insights into cancer hallmarks - Pin-Rong Chen; Tz-Syuan Su; Kun-Che Chang; Chien-Chih Chiu; Shu-Pin Huang; Hsin-Chih Yeh; Shu-Chi Wang; Chia-Yang Li (Phytochemistry Reviews, 2026)

A method for detecting transgenic rapeseed using pollen collected by Apis mellifera L - Rong Yuan; Miao Wang; Zhen Li; Meiyan Hong; Li Su; Gang Wu; Xinhua Zeng (Transgenic Research, 2025)

Temporin-GHaR Peptide Alleviates LPS-Induced Cognitive Impairment and Microglial Activation by Modulating Endoplasmic Reticulum Stress - Da-Qi Zhang; Xiaoqian Dong; Simin Su; Linlin Zhang; Jiayu Zhang; Wenjing Yang; Wenting Hu; Lushuang Li; Yanting Song; Xi Xie; Qifu Li; Rong Wang; et al. (Probiotics and Antimicrobial Proteins, 2025)

Interactions between soil and phyllosphere microbiomes modulate flavor formation of Qingxiang Tieguanyin Oolong Tea - Zhao Zhang; Xin-Rong Huang; Ming-Kang Jin; Le-Yang Yang; Jing-Jun Deng; Hu Li; Zhi-Ming Chen; Huo-Gui Su; Liang-De Xiao; Jin-Long Tang; Shun Li; Roy Neilson; et al. (Plant and Soil, 2025)

The effect of soil microbial functional groups, abiotic and biotic factors on plant functional groups: insights from a tropical rainforest in Southwest China - Yanxuan Chen; Xiaobo Huang; Rong Tang; Rui Zhang; Cong Li; Tongli Wang; Jianrong Su; Shuaifeng Li (Plant and Soil, 2025)

Subseasonal Prediction Skill in the CAMS-CSM Subseasonal-to-Seasonal Forecast System - Yuhan Yan; Jingzhi Su; Boqi Liu; Libin Ma; Xinyao Rong; Bo Liu; Yanli Tang; Jian Li (Advances in Atmospheric Sciences, 2025)

ADAMDEC1 promotes cervical squamous cell carcinoma by enhancing the JAK/STAT signaling pathway through modulation of TYMP - Beibei Wang; Qingsong Zhang; Lihua Wang; Huiwen Su; Li Zhou; Rong Zhang; Qiangkun Wan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Identification of Potential Causal Genes for Neurodegenerative Diseases by Mitochondria-Related Genome-Wide Mendelian Randomization - Kang-Fu Yin; Ting Chen; Xiao-Jing Gu; Zheng Jiang; Wei-Ming Su; Qing-Qing Duan; Xiang-Jin Wen; Bei Cao; Ju-Rong Li; Li-Yi Chi; Yong-Ping Chen (Molecular Neurobiology, 2025)

Advancing treatment strategies against MRSA: unveiling the potency of tubuloside A in targeting sortase A and mitigating pathogenicity - Yangming Xu; Yanhe Luan; Rong Wang; Zhengjie Su; Li Wang; Yinghui Liu; Guangzhi Jiang; Bingmei Wang (World Journal of Microbiology and Biotechnology, 2025)

Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

Multiple NADPH-cytochrome P450 reductases from Lycoris radiata involved in Amaryllidaceae alkaloids biosynthesis - Yuqing Wu; Yifeng Zhang; Haitong Fan; Jie Gao; Siyu Shen; Jifan Jia; Rong Liu; Ping Su; Yating Hu; Wei Gao; Dan Li (Plant Molecular Biology, 2024)

Influenza A Virus PB1-F2 Induces Affective Disorder by Interfering Synaptic Plasticity in Hippocampal Dentate Gyrus - Saiying Wang; Haijun Zhang; Rui Liu; Peijun Han; Qi Yang; Caiyan Cheng; Yue Chen; Zheng Rong; Chang Su; Fei Li; Gaofei Wei; Minggao Zhao; et al. (Molecular Neurobiology, 2024)

Cloning and functional identification of anthocyanin synthesis-regulating transcription factor AaMYB4 in Aeonium arboreum Webb & Berthel ‘Halloween’ - Rong Zhao; Su-Hua Li; Hao-Zhang Han; Li-Hua Zhang; Fang Wang; Nan Zhang (Brazilian Journal of Botany, 2024)

Strong ground motion characteristics of the 2022 MW 6.6 Luding earthquake and regional variability in ground motion among three earthquake areas in Sichuan, Southwest China - Bin Zhang; Xiaojun Li; Yanxiang Yu; Xiaojian Lu; Mianshui Rong; Su Chen; Zhao An; Zhenghui Xiong (Bulletin of Earthquake Engineering, 2024)

Expert Consensus on Big Data Collection of Skin and Appendage Disease Phenotypes in Chinese - Shuang Zhao; Zhongling Luo; Ying Wang; Xinghua Gao; Juan Tao; Yong Cui; Aijun Chen; Daxing Cai; Yan Ding; Heng Gu; Jianying Gu; Chao Ji; et al. (Phenomics, 2024)

Nitidine chloride regulates cell function of bladder cancer in vitro through downregulating Lymphocyte antigen 75 - Shi-shuo Wang; Gao-qiang Zhai; Zhi-guang Huang; Jia-yuan Luo; Juan He; Jie-zhuang Huang; Ling Yang; Chu-nan Xiao; Su-li Li; Kai-rong Chen; Yan-yu Chen; Han-chu Ji; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

The association between greenery type and gut microbiome in schizophrenia: did all greenspaces play the equivalent role? - Ning Wei; Shusi Wang; Xuanxuan Li; Rubing Pan; Weizhuo Yi; Jian Song; Li Liu; Jintao Liu; Jiajun Yuan; Rong Song; Jian Cheng; Hong Su (Environmental Science and Pollution Research, 2023)

Shape Classification of Cloud Particles Recorded by the 2D-S Imaging Probe Using a Convolutional Neural Network - Rong Zhang; Haixia Xiao; Yang Gao; Haizhou Su; Dongnan Li; Lei Wei; Junxia Li; Hongyu Li (Journal of Meteorological Research, 2023)

Synergistic effect of elevated glucose levels with SARS-CoV-2 spike protein induced NOX-dependent ROS production in endothelial cells - Jiahao Zhang; Li He; Rong Huang; Juan Felipe Alvarez; David H. Yang; Qihao Sun; Fengqin Wang; Zhiyong Peng; Nanhui Jiang; Lianjiu Su (Molecular Biology Reports, 2023)

SHP2: its association and roles in systemic lupus erythematosus - Chan Yang; Rong Li; Lin-Chong Su; You-Yu Lan; You-Qiang Wang; Wang-Dong Xu; An-Fang Huang (Inflammation Research, 2023)

Characterization of airborne microplastics at different workplaces of the poly(ethylene:propylene:diene) (EPDM) rubber industry - Xiaoni Sun; Rong Song; Jintao Liu; Shuangshuang Yan; Yuxuan Li; Xiaoyu Jin; Yunfeng Liang; Yudong Wu; Lu Mei; Rubing Pan; Weizhuo Yi; Jian Song; et al. (Environmental Science and Pollution Research, 2023)

Environmental Factors Influence the Effects of Biochar on the Bioavailability of Cd and Pb in Soil Under Flooding Condition - Honghong Li; Zhou Li; Limei Huang; Xiaoming Mao; Yuxuan Dong; Shilong Fu; Rong Su; Yihan Chang; Chuan Zhang (Water, Air, & Soil Pollution, 2023)

In situ phytostabilization of arable soils severely contaminated with cadmium at Yangshuo, Southern China, using cash crops and amendments: a comprehensive performance evaluation - Bo-Fang Yan; Mei-Lin Yan; Xue Xiao; Rong-Liang Qiu; Yuan-Qing Chao; Yin-Xin Li; Su-Lian Lv; Zhong-Xin Tan; Ye-Tao Tang (Journal of Soils and Sediments, 2023)

Screening of microRNA and mRNA related to secondary hair follicle morphogenesis and development and functional analysis in cashmere goats - Fangzheng Shang; Yu Wang; Rong Ma; Youjun Rong; Min Wang; Zhihong Wu; Erhan Hai; Jianfeng Pan; Lili Liang; Zhiying Wang; Ruijun Wang; Rui Su; et al. (Functional & Integrative Genomics, 2022)
microRNA (miRNA) is a type of endogenous short-chain non-coding RNA with regulatory function found in eukaryotes, which is involved in the regulation of a variety of cellular and biological processes. However, the research on the development of cashmere goat secondary hair follicles is still relatively scarce. In this study, small RNA libraries and mRNA libraries of 45 days, 55 days, 65 days, and 75 days of fetal skin of cashmere goats were constructed, and the constructed libraries were sequenced using Illumina Hiseq4000, and the expression profiles of miRNA and mRNA in cashmere goat fetal skin were obtained. The differentially expressed miRNAs and mRNAs in six control groups were identified and the qRT-PCR experiment shows that the sequencing results are accurate. Sixty-six miRNAs related to secondary hair follicle development were screened, and used TargetScan and miRanda to predict 33 highly expressed miRNA target genes. At the same time, 664 mRNAs related to the development of secondary hair follicles were screened, and GO enrichment and KEGG pathway analysis were performed. It was found that some miRNA target genes were consistent with the screening results of mRNAs related to secondary hair follicle development and were enriched in Notch signaling pathway, TGF-β signaling pathway. Therefore, miR-145-5p-DLL4, miR-27b-3p-DLL4, miR-30e-5p-DLL4, miR-193b-3p-TGF-β1, miR-181b-5p-NOTCH2, and miR-103-3p-NOTCH2 regulatory network related to the development of secondary hair follicles were constructed and the results of dual-luciferase reporter gene assay indicated that there is a targeted relationship between chi-miR-30e-5p and DLL4, which will provide a basis for molecular mechanism of miRNA-mRNA in the development of the hair follicles in cashmere goats.

Heat Shock Procedure Affects Cell Division-Associated Genes in Gynogenetic Manipulation - Fan Yu; Jian-Lin Li; Wen-Rong Feng; Yong-Kai Tang; Sheng-Yan Su; Pao Xu; Huan Zhong (Marine Biotechnology, 2022)

Seasonal prediction skills in the CAMS-CSM climate forecast system - Bo Liu; Jingzhi Su; Libin Ma; Yanli Tang; Xinyao Rong; Jian Li; Haoming Chen; Boqi Liu; Lijuan Hua; Renguang Wu (Climate Dynamics, 2021)

Mixing overstory tree- and understory fern-derived dissolved organic carbon produces non-additive effects on biodegradation in subtropical forests of southern China - Su-Li Li; Zhi Zheng; Yi-Dong Ding; Jia-Wen Xu; Rong Mao (Plant and Soil, 2021)

Identification of two UDP-glycosyltransferases involved in the main oleanane-type ginsenosides in Panax japonicus var. major - Jun-Rong Tang; Geng Chen; Ying-Chun Lu; Qing-Yan Tang; Wan-Ling Song; Yuan Lin; Ying Li; Su-Fang Peng; Sheng-Chao Yang; Guang-Hui Zhang; Bing Hao (Planta, 2021)

Effects of simulated drought stress on carotenoid contents and expression of related genes in carrot taproots - Rong-Rong Zhang; Ya-Hui Wang; Tong Li; Guo-Fei Tan; Jian-Ping Tao; Xiao-Jun Su; Zhi-Sheng Xu; Yong-Sheng Tian; Ai-Sheng Xiong (Protoplasma, 2021)

Specific protein 1 inhibitor mithramycin A protects cardiomyocytes from myocardial infarction via interacting with PARP - Haihua Geng; Yamin Su; Rong Huang; Mengkang Fan; Xiaofei Li; Xiaochen Lu; Hongzhuan Sheng (In Vitro Cellular & Developmental Biology - Animal, 2021)

Relationship Between Body Composition and Balance Performance in Older Adults with Hyperkyphosis - Phunsuk Kantha; Shiow-Chwen Tsai; Chien-Wen Hou; Rong-Sen Yang; Pei-Yu Su; Wei-Li Hsu (Journal of Medical and Biological Engineering, 2021)

The CMIP6 Historical Simulation Datasets Produced by the Climate System Model CAMS-CSM - Xinyao Rong; Jian Li; Haoming Chen; Jingzhi Su; Lijuan Hua; Zhengqiu Zhang; Yufei Xin (Advances in Atmospheric Sciences, 2021)
This paper describes the historical simulations produced by the Chinese Academy of Meteorological Sciences (CAMS) climate system model (CAMS-CSM), which are contributing to phase 6 of the Coupled Model Intercomparison Project (CMIP6). The model description, experiment design and model outputs are presented. Three members’ historical experiments are conducted by CAMS-CSM, with two members starting from different initial conditions, and one excluding the stratospheric aerosol to identify the effect of volcanic eruptions. The outputs of the historical experiments are also validated using observational data. It is found that the model can reproduce the climatological mean states and seasonal cycle of the major climate system quantities, including the surface air temperature, precipitation, and the equatorial thermocline. The long-term trend of air temperature and precipitation is also reasonably captured by CAMS-CSM. There are still some biases in the model that need further improvement. This paper can help the users to better understand the performance and the datasets of CAMS-CSM.

Leptin promotes endothelial dysfunction in chronic kidney disease by modulating the MTA1-mediated WNT/β-catenin pathway - Bing Liu; Jiao Qiao; Jinxiu Hu; Minghua Fan; Yanfang Zhao; Hong Su; Ziyang Wang; Qun Yu; Qiqi Ma; Yanmei Li; Zhimei Lv; Rong Wang (Molecular and Cellular Biochemistry, 2020)

SNP discovery in Mauremys reevesii and M. sinensis using restriction site-associated DNA sequence (RAD-seq) - Qiming Xie; Chaozhen Rong; Xilei Li; Nianyue Lai; Tiantian Chen; Qingqing Li; Shiping Su (Conservation Genetics Resources, 2020)

Obtaining More Information about Precipitation Biases over East Asia from Hourly-Scale Evaluation of Model Simulation - Nina Li; Jian Li; Xinyao Rong; Haoming Chen; Yufei Xin; Jingzhi Su (Journal of Meteorological Research, 2020)

Method for obtaining high-resolution velocity spectrum based on weighted similarity - Xing-Rong Xu; Qin Su; Jun-Fa Xie; Jing Wang; Long-Jiang Kou; Meng-Li Liu (Applied Geophysics, 2020)

Physiological and proteomic responses of mangrove plant Avicennia marina seedlings to simulated periodical inundation - Huan Li; Zan Li; Zhi-Jun Shen; Mei-Rong Luo; Yi-Ling Liu; Ming-Yue Wei; Wen-Hua Wang; Ying-Ying Qin; Chang-Hao Gao; Ke-Ke Li; Qian-Su Ding; Shan Zhang; et al. (Plant and Soil, 2020)

Immunogenicity noninferiority study of 2 doses and 3 doses of an Escherichia coli-produced HPV bivalent vaccine in girls vs. 3 doses in young women - Yue-Mei Hu; Meng Guo; Chang-Gui Li; Kai Chu; Wen-Gang He; Jing Zhang; Jian-Xiang Gu; Juan Li; Hui Zhao; Xiang-Hong Wu; BiZhen Lin; Zhi-Jie Lin; et al. (Science China Life Sciences, 2020)

Expression of the kisspeptin/gonadotropin-releasing hormone (GnRH) system in the brain of female Chinese sucker (Myxocyprinus asiaticus) at the onset of puberty - Shiping Su; Qingqing Li; Xilei Li; Chaozhen Rong; Qiming Xie (Fish Physiology and Biochemistry, 2020)

Root diversity in sesame (Sesamum indicum L.): insights into the morphological, anatomical and gene expression profiles - Ruqi Su; Rong Zhou; Marie Ali Mmadi; Donghua Li; Lu Qin; Aili Liu; Jianqiang Wang; Yuan Gao; Mengyuan Wei; Lisong Shi; Ziming Wu; Jun You; et al. (Planta, 2019)

Convectively Coupled Equatorial Waves Simulated by CAMS-CSM - Lu Wang; Tianjun Zhou; Jian Li; Xinyao Rong; Haoming Chen; Yufei Xin; Jingzhi Su (Journal of Meteorological Research, 2019)

Allopolyploidization facilitates gene flow and speciation among corn, Zea perennis and Tripsacum dactyloides - Muhammad Zafar Iqbal; Mingjun Cheng; Yuegui Su; Yang Li; Weiming Jiang; Huaxiong Li; Yanli Zhao; Xiaodong Wen; Lei Zhang; Asif Ali; Tingzhao Rong; Qilin Tang (Planta, 2019)

In Vitro Susceptibility of Berberine Combined with Antifungal Agents Against the Yeast Form of Talaromyces marneffei - Hong Luo; Kai-su Pan; Xiao-lu Luo; Dong-yan Zheng; Alex Andrianopoulos; Le-min Wen; Yan-qing Zheng; Jing Guo; Chun-yang Huang; Xiu-ying Li; Rong Hu; Yu-jiao Li; et al. (Mycopathologia, 2019)

Neuroprotective effects of matrine on scopolamine-induced amnesia via inhibition of AChE/BuChE and oxidative stress - Kaiyue Sun; Yuting Bai; Rong Zhao; Zijiao Guo; Xiang Su; Peiqi Li; Pengyu Yang (Metabolic Brain Disease, 2019)

Climate Sensitivity and Feedbacks of a New Coupled Model CAMS-CSM to Idealized CO2 Forcing: A Comparison with CMIP5 Models - Xiaolong Chen; Zhun Guo; Tianjun Zhou; Jian Li; Xinyao Rong; Yufei Xin; Haoming Chen; Jingzhi Su (Journal of Meteorological Research, 2019)

A Longitudinal Functional Magnetic Resonance Imaging Study of Working Memory in Patients Following a Transient Ischemic Attack: A Preliminary Study - Wei Su; Jian Guo; Yun Zhang; Jie Zhou; Ning Chen; Muke Zhou; Rong Li; Huafu Chen; Li He (Neuroscience Bulletin, 2018)

The CAMS Climate System Model and a Basic Evaluation of Its Climatology and Climate Variability Simulation - Xinyao Rong; Jian Li; Haoming Chen; Yufei Xin; Jingzhi Su; Lijuan Hua; Tianjun Zhou; Yanjun Qi; Zhengqiu Zhang; Guo Zhang; Jianduo Li (Journal of Meteorological Research, 2018)

An Assessment of CAMS-CSM in Simulating Land–Atmosphere Heat and Water Exchanges - Guo Zhang; Jianduo Li; Xinyao Rong; Yufei Xin; Jian Li; Haoming Chen; Jingzhi Su; Lijuan Hua (Journal of Meteorological Research, 2018)

Impact of atmospheric model resolution on simulation of ENSO feedback processes: a coupled model study - Lijuan Hua; Lin Chen; Xinyao Rong; Jingzhi Su; Lu Wang; Tim Li; Yongqiang Yu (Climate Dynamics, 2018)

Seasonal Variation and Exposure Risks of Perchlorate in Soil, Indoor Dust, and Outdoor Dust in China - Yiwen Li; Ruoying Liao; Zhiwei Gan; Bing Qu; Rong Wang; Mengqin Chen; Sanglan Ding; Shijun Su (Archives of Environmental Contamination and Toxicology, 2018)

De novo transcriptome analysis of an albino mutant Pasphiopedilum pacific shamrock reveals reduced expression of genes related to chloroplast biosynthesis and division - Han Li; Hua Cao; Rong-pei Yu; Zhen Miao; Ji-hua Wang; Su-Ping Qu; Qiang Yuan; Shen-chong Li (Horticulture, Environment, and Biotechnology, 2018)

Nutrient Decomposition Rate and Sugarcane Yield as Influenced by Mung Bean Intercropping and Crop Residue Recycling - Tie-Guang He; Li-Rong Su; Yang-Rui Li; Tian-Ming Su; Fang Qin; Qin Li (Sugar Tech, 2018)

Study on the influential biochemical indices of Cd(II) on Eisenia fetida in oxidative stress by principal component analysis in the natural soil - Yucui Ning; Liyan Liu; Guohua Rong; Xu Cao; Jing Li; Ye Su; Dongxing Zhou (Environmental Science and Pollution Research, 2018)

Exploration of the formation mechanism and source attribution of ambient ozone in Chongqing with an observation-based model - Rong Su; KeDing Lu; JiaYan Yu; ZhaoFeng Tan; MeiQing Jiang; Jing Li; ShaoDong Xie; YuSheng Wu; LiMin Zeng; ChongZhi Zhai; YuanHang Zhang (Science China Earth Sciences, 2018)

Concentrations and Exposure Evaluation of Metals in Diverse Food Items from Chengdu, China - Rong Wang; Bifeng Zhong; Lu Pi; Fuyu Xie; Mengqin Chen; Sanglan Ding; Shijun Su; Zhi Li; Zhiwei Gan (Archives of Environmental Contamination and Toxicology, 2018)

Erratum to: Activation of the ventral tegmental area increased wakefulness in mice - Huan-Xin Sun; Dian-Ru Wang; Chen-Bo Ye; Zhen-Zhen Hu; Chen-Yao Wang; Zhi-Li Huang; Su-Rong Yang (Sleep and Biological Rhythms, 2017)

Characterization of extracellular polymeric substance (EPS) fractions produced by Microcystis aeruginosa under the stress of linoleic acid sustained-release microspheres - Lixiao Ni; Danye Li; Shiyi Rong; Lili Su; Wei Zhou; Peifang Wang; Chao Wang; Shiyin Li; Kumud Acharya (Environmental Science and Pollution Research, 2017)

Reduced weed seed shattering by silencing a cultivated rice gene: strategic mitigation for escaped transgenes - Huanxin Yan; Lei Li; Ping Liu; Xiaoqi Jiang; Lei Wang; Jia Fang; Zhimin Lin; Feng Wang; Jun Su; Bao-Rong Lu (Transgenic Research, 2017)

Lower functional connectivity of default mode network in cognitively normal young adults with mutation of APP, presenilins and APOE ε4 - Yun Yan Su; Xiao Dong Zhang; U. Joseph Schoepf; Akos Varga-Szemes; Andrew Stubenrauch; Xue Liang; Li Juan Zheng; Gang Zheng; Xiang Kong; Qiang Xu; Shou Ju Wang; Rong Feng Qi; et al. (Brain Imaging and Behavior, 2017)

Activation of the ventral tegmental area increased wakefulness in mice - Huan-Xin Sun; Dian-Ru Wang; Chen-Bo Ye; Zhen-Zhen Hu; Chen-Yao Wang; Zhi-Li Huang; Su-Rong Yang (Sleep and Biological Rhythms, 2017)

Oral administration of Schisandra chinensis extract suppresses Dnmt1 expression in Kunming mice ovaries - Feng-Rui Wu; Deng-kun Li; Mi-mi Su; Yong Liu; Biao Ding; Rong Wang; Wen-yong Li (Genes & Genomics, 2016)

CGRP 8-37 enhances lipopolysaccharide-induced acute lung injury and regulating aquaporin 1 and 5 expressions in rats - Fu Hong-min; Huangfu Chun-rong; Zheng Rui; Su Li-na; Wang Ya-jun; Li Li (Journal of Physiology and Biochemistry, 2016)

Age-related changes in photosynthesis and water relations of revegetated Caragana korshinskii in the Tengger desert, Northern China - Jing-Ting Bao; Jin Wang; Xin-Rong Li; Zhi-Shan Zhang; Jie-Qiong Su (Trees, 2015)

Modified method for estimating organic carbon density in discontinuous Karst soil using ground-penetrating radar and geostatistics - Lei Li; Yin-hang Xia; Shu-juan Liu; Wei Zhang; Xiang-bi Chen; Hua Zheng; Hu-sen Qiu; Xun-yang He; Yi-rong Su (Journal of Mountain Science, 2015)

Bacteriological and virulence study of a Mycobacterium chimaera isolate from a patient in China - Guan Liu; Su-Ting Chen; Xia Yu; Yu-Xun Li; Ying Ling; Ling-Ling Dong; Su-Hua Zheng; Hai-Rong Huang (Antonie van Leeuwenhoek, 2015)

Soil cellulase activity and fungal community responses to wetland degradation in the Zoige Plateau, China - Li-sha Wu; Su Feng; Yuan-yang Nie; Jian-hong Zhou; Zhi-rong Yang; Jie Zhang (Journal of Mountain Science, 2015)

The anti-angiogenic role of discoidin domain receptor 2 (DDR2) in laser-induced choroidal neovascularization - Tong Zhu; Jie Zhu; Xin Bu; Hu Zhao; Shuya Zhang; Yuan Chang; Rong Li; Libo Yao; Yusheng Wang; Jin Su (Journal of Molecular Medicine, 2015)

Separation of the impact of climate change and human activity on streamflow in the upper and middle reaches of the Taoer River, northeastern China - Bin Li; Hongbo Su; Fang Chen; Haibin Li; Renhua Zhang; Jing Tian; Shaohui Chen; Yongming Yang; Yuan Rong (Theoretical and Applied Climatology, 2014)

Antigenic variability among two subtypes of human adenovirus serotype 7 - Xingui Tian; Xiaobo Su; Chunyan Xue; Xiao Li; Zhichao Zhou; Rong Zhou (Virus Genes, 2014)

Effect of NeuroD Gene Silencing on the Migration and Invasion of Human Pancreatic Cancer Cells PANC-1 - Yang Wang; Dong Wei Su; Li Gao; Gui Ling Ding; Can Rong Ni; Ming Hua Zhu (Cell Biochemistry and Biophysics, 2014)

Effects of land cover on soil organic carbon stock in a karst landscape with discontinuous soil distribution - Xiang-bi Chen; Hua Zheng; Wei Zhang; Xun-yang He; Lei Li; Jin-shui Wu; Dao-you Huang; Yi-rong Su (Journal of Mountain Science, 2014)

Isolation and characterization of microsatellite loci in the clam Lutraria sieboldii Reeve (Bivalvia: Veneroida) - Xiang-Ju Su; Ying Pan; Zi-Rong Zuo; Ling-Feng Kong; Qi Li (Conservation Genetics Resources, 2013)

The changing pattern of droughts in the Lancang River Basin during 1960–2005 - Bin Li; Hongbo Su; Fang Chen; Shenggong Li; Jing Tian; Yuchu Qin; Renhua Zhang; Shaohui Chen; Yongming Yang; Yuan Rong (Theoretical and Applied Climatology, 2013)

Molecular epidemiology of PRRSV from China’s Guangxi Province between 2007 and 2009 - Hong-Yun Zhang; Jing-Jing Liang; Xian-Ming Meng; Hui Li; Jian Yang; Li-Juan Su; Hong-Pu Zhang; Lin-Juan Xie; Xiao-Xia He; Yan-Sheng Li; Shan Yin; Xiao-Quan Li; et al. (Virus Genes, 2013)

Tectonic mechanism of the Suining (Ms5.0) earthquake, center of Sichuan Basin, China - Rong-jun Zhou; Yong Li; Laurence Svirchev; Yong-jiu Zhang; Deng-fa He; Yu-lin He; Pei-lin Zhao; Zan-jun Wang; Feng Long; Jin-rong Su; Shi-yuan Wang; Ming-jian Liang; et al. (Journal of Mountain Science, 2013)

Episodic orogeny deduced from coeval sedimentary sequences in the foreland basin and its implication for uplift process of Longmen Mountain, China - Yong Li; De-chen Su; Rong-jun Zhou; Hai-bing Li; Alexander L. Densmore; Liang Yan; Zhao-kun Yan (Journal of Mountain Science, 2013)

Characterization of a Novel Pollen-Specific Promoter from Wheat (Triticum Aestivum L.) - Ling Chen; Yingjie Miao; Cheng Wang; Peipei Su; Tianheng Li; Rong Wang; Xinglong Hao; Guangxiao Yang; Guangyuan He; Chunbao Gao (Plant Molecular Biology Reporter, 2012)

Polymorphisms of the interleukin-15 gene and their associations with fatness and muscle fiber traits in chickens - Shi-Jie Lv; Ling Su; Hong Li; Rui-Li Han; Gui-Rong Sun; Xiang-Tao Kang (Journal of Applied Genetics, 2012)

Association of PDE4B polymorphisms and schizophrenia in Northwestern Han Chinese - Fanglin Guan; Chen Zhang; Shuguang Wei; Hongbo Zhang; Xiaomin Gong; Jiali Feng; Chengge Gao; Rong Su; Huanming Yang; Shengbin Li (Human Genetics, 2012)

Phylogenetic analysis of the E2 gene of classical swine fever virus from the Guangxi Province of southern China - Ting Rong Luo; Su-huan Liao; Xian-shi Wu; Li Feng; Zhao-Xia Yuan; Hui Li; Jing-Jing Liang; Xian-Ming Meng; Hong-Yun Zhang (Virus Genes, 2011)

Immunomodulative effects of mesenchymal stem cells derived from human embryonic stem cells in vivo and in vitro - Zhou Tan; Zhong-yuan Su; Rong-rong Wu; Bin Gu; Yu-kan Liu; Xiao-li Zhao; Ming Zhang (Journal of Zhejiang University-SCIENCE B, 2011)

Laser altimetry data of Chang’E-1 and the global lunar DEM model - ChunLai Li; Xin Ren; JianJun Liu; XiaoDuan Zou; LingLi Mu; JianYu Wang; Rong Shu; YongLiao Zou; HongBo Zhang; Chang Lü; JianZhong Liu; Wei Zuo; et al. (Science China Earth Sciences, 2010)

The phylogeny analysis of MyoG gene in different pig breeds - Li Zhu; Xue-Wei Li; Su-Rong Shuai; Ming-Zhou Li; Lei Chen; Yi-Ren Gu; Kai Zhang (Interdisciplinary Sciences: Computational Life Sciences, 2010)

Genetic Diversity and Geographical Differentiation of Desmodium triflorum (L.) DC. in South China Revealed by AFLP Markers - Mao-feng Yue; Ren-chao Zhou; Ye-lin Huang; Guo-rong Xin; Su-hua Shi; Li Feng (Journal of Plant Biology, 2010)

Isolation and characterization of microsatellite markers for the endangered Taxus yunnanensis - Ying-Chun Miao; Jian-Rong Su; Zhi-Jun Zhang; Hui Li; Jing Luo; Ya-Ping Zhang (Conservation Genetics, 2008)

Phytase expression in transgenic soybeans: stable transformation with a vector-less construct - Xiao Rong Gao; Guo Kun Wang; Qiao Su; Yan Wang; Li Jia An (Biotechnology Letters, 2007)

Morphological changes of cholinergic nerve fibers in the urinary bladder after establishment of artificial somatic-autonomic reflex arc in rats - Han-Zhi Wang; Shu-Rong Li; Can Wen; Chuan-Guo Xiao; Bing-Yin Su (Neuroscience Bulletin, 2007)

Effects of biological soil crusts on emergence of desert vascular plants in North China - Yan-Gui Su; Xin-Rong Li; Ying-Wu Cheng; Hui-Juan Tan; Rong-Liang Jia (Plant Ecology, 2007)

Unexpected effect of concomitantly administered curcumin on the pharmacokinetics of talinolol in healthy Chinese volunteers - He Juan; Bernd Terhaag; Zang Cong; Zhang Bi-Kui; Zhu Rong-Hua; Wang Feng; Su Fen-Li; Song Juan; Tang Jing; Peng Wen-Xing (European Journal of Clinical Pharmacology, 2007)

Dynamics in microbial immobilization and transformations of phosphorus in highly weathered subtropical soil following organic amendments - Jinshui Wu; Min Huang; He-Ai Xiao; Yi-Rong Su; Cheng-Li Tong; Dao-You Huang; J. Keith Syers (Plant and Soil, 2007)